Comparative study of single- and double-layer BaFe12O19-Graphite nanocomposites for electromagnetic wave absorber applications - Ismail I.; Ibrahim I.R.; Matori K.A.; Awang Z.; Muhammad Zulkimi M.M.; Mohd Idris F.; Nazlan R.; Azis R.S.; Mohd Zaid M.H.; Rusly S.N.A.; Ertugrul M. (Pergamon-Elsevier Science Ltd, 2024)
Indexed by WOS/Scopus/ERA